VD_FINDINFO HC / 2018 / 495 vom 13. Juni 2018 - VD Tribunal cantonal (2018)
PARTENARIAT ENREGISTRÉ, ANNULABILITÉ, OBLIGATION D'ENTRETIEN, PRÉVOYANCE PROFESSIONNELLE | 33 LPart, 34 LPart, 9 LPart, 223 al. 2 CPC (CH), 69 al. 1 CPC (CH)